The effect of voluntary hypoventilation in yoga breathing exercises on gas exchange and EEG activity in healthy trained subjects - A. V. Frolov; J. A. Boytsova; S. A. Ermolaeva; M. D. Didur (National Electronic Information Consortium (NEICON), 2023)
Objective: to assess the effect of voluntary hypoventilation during yoga breathing exercises on gas exchange and EEG activity in a group of healthy, trained practitioners.Materials and methods: 25 volunteers (21 men and 4 women, average age 42.96 ± 9.19 years) performed hypoventilation yoga exercises with a decrease in respiratory rate to 1-1.5 times/minute. Registration of respiratory rate, tidal volume and minute volume of breathing, gas analysis of exhaled air (PetCO2, FeO2) and spectral analysis of electroencephalogram (EEG) in gICA model were carried out during breathing with a frequency of 1-1.5 times/minute and during relatively free breathing with mental calculation.Results: Breathing with a frequency of 1-1.5 times/minute causes a decrease in minute volume of breathing, the development of alveolar hypoxia and hypercapnia, which leads to an increase in the power of some local components in the slow delta, theta and alpha EEG bands. In addition, breathing with a frequency of 1-1.5 times/minute is accompanied by a decrease in the alpha- and beta-power of some components, the sources of which are located in the motor areas of the cortex, but is also accompanied by an increase in the power of components with widespread scalp topography in beta and gamma bands.Conclusion: Voluntary hypoventilation during yoga breathing exercises leads to the development of alveolar hypoxia and hypercapnia, accompanied by an increase in the power of local components in the slow EEG bands. At the same time, the alpha and beta powers of components localized in the motor areas of the cortex decrease, which may be a consequence of muscle tension during slow breathing.